Visualization and Identification of Bioorthogonally Labeled Exosome Proteins Following Systemic Administration in Mice - Zhang, Eric; Liu, Yanwen; Han, Chaoshan; Fan, Chengming; Wang, Lu; Chen, Wangping; Du, Yipeng; Han, Dunzheng; Arnone, Baron; Xu, Shiyue; Wei, Yuhua; Mobley, James; et al. (Frontiers in Cell and Developmental Biology, 2021)
Exosomes transport biologically active cargo (e.g., proteins and microRNA) between cells, including many of the paracrine factors that mediate the beneficial effects associated with stem-cell therapy. Stem cell derived exosomes, in particular mesenchymal stem cells (MSCs), have been shown previously to largely replicate the therapeutic activity associated with the cells themselves, which suggests that exosomes may be a useful cell-free alternative for the treatment of cardiovascular disorders. However, the mechanisms that govern how exosomes home to damaged cells and tissues or the uptake and distribution of exosomal cargo are poorly characterized, because techniques for distinguishing between exosomal proteins and proteins in the targeted tissues are lacking. Here, we report the development of an in-vivo model that enabled the visualization, tracking, and quantification of proteins from systemically administered MSC exosomes. The model uses bioorthogonal chemistry and cell-selective metabolic labeling to incorporate the noncanonical amino acid azidonorleucine (ANL) into the MSC proteome. ANL incorporation is facilitated via expression of a mutant (L274G) methionyl-tRNA-synthetase (MetRS*) and subsequent incubation with ANL-supplemented media; after which ANL can be covalently linked to alkyne-conjugated reagents (e.g., dyes, resins) via click chemistry. Our results demonstrate that when the exosomes produced by ANL-treated, MetRS*-expressing MSCs were systemically administered to mice, the ANL-labeled exosomal proteins could be accurately and reliably identified, isolated, and quantified from a variety of mouse organs, and that myocardial infarction (MI) both increased the abundance of exosomal proteins and redistributed a number of them from the membrane fraction of intact hearts to the cytosol of cells in infarcted hearts. Additionally, we found that Desmoglein-1c is enriched in MSC exosomes and taken up by ischemic myocardium. Collectively, our results indicate that this newly developed bioorthogonal system can provide crucial insights into exosome homing, as well as the uptake and biodistribution of exosomal proteins.